Inventing the world grant university: Chinese international students' mobilities, literacies, and identities - Fraiberg, Steven, author; Wang, Xiqiao, author; You, Xiaoye, author; Utah State University Press, publisher (Colorado State University. Libraries, 2017)
Culturally responsive pedagogies developed for undergraduate Chinese international students, who have enrolled in Western institutions in increasing numbers in recent years. Focusing on the literacy practices of these students at Michigan State University and at Sinoway International Educational Summer School in China, Fraiberg.--Provided by publisher.
Friction in the educational marketplace -- Geographies of difference: underground knotworks and transnational social fields -- Relationship webs in academic lives -- Learning lords and scumbags: underground literacies and learning economies -- Study abroad at home -- Assembling the cosmopolitan -- Gaming life like outlaws.
In English with passages in Chinese with English translation.
Keywords: Chinese students -- Education (Higher) -- Western countries; Chinese students -- Foreign countries; Culturally relevant pedagogy